Effect of hospital‐wide interventions to optimize albumin use in a tertiary hospital. (9th June 2017) - Laki, B.; Taghizadeh‐Ghehi, M.; Assarian, M.; Heidari, K.; Torkamandi, H.; Javadi, M. R.; Gholami, K.
Summary: What is known and objective: Albumin has been frequently used as a therapeutic agent based on previous recommendations that are mostly controversial. Considering limited evidence‐based indications, common inappropriate albumin use in many hospitals necessitates prompt educational and regulatory interventions. We performed this study to assess the effect of a hospital‐wide programme to optimize albumin use in a tertiary referral university‐affiliated hospital. Methods: This study was conducted in three 45‐day phases, separated by two sequential interventions: guideline implementation and albumin order‐sheet consideration. We evaluated albumin use and assessed its appropriateness in each phase at baseline, after guideline implementation and after order‐sheet consideration. Results: We recorded 100, 93 and 71 albumin orders for 100, 84 and 66 patients during the first, second and third phases, respectively. The adjusted number of albumin orders (used albumin vials) was 94.9 (1481.7 vials), 80.8 (1037.6 vials) and 66 (1219 vials) in the first, second and third phases of the study, respectively. Albumin orders with appropriate indication increased significantly over the three phases of the study (OR=1.5, P =.008). The frequency of inappropriate orders reduced significantly from the first phase to the third phase (58%‐27%, P =.007). What is new and conclusion: The pattern and amount of albumin use changed following guideline implementation and order‐sheet consideration, and inappropriate albumin use was reduced in our hospital. There was still room for improvement, particularly for indications that were not included in the guideline. Hence, a more comprehensive guideline, frequent audit, feedback and interactive educational approaches might be necessary to achieve results that are of a greater magnitude. Abstract : Although albumin has limited evidence‐based uses, it is used frequently for inappropriate indications in many hospitals. We performed this study to assess the effect of two sequential interventions: guideline implementation and albumin order‐sheet consideration, to optimize albumin use in a tertiary hospital. Appropriate albumin use, showed an increasing trend during the study phases. We did not observe the expected changes considering occasionally appropriate indications that were not included in the guideline.